Decolonizing an African art collection in Canada? Reflections on the exhibition "Stories to Tell: Africans and the Diaspora Respond to the Lang Collection, " 2016–2018. Issue 1 (2nd January 2022) - Goebel, Allison; Epprecht, Marc
ABSTRACT: This paper discusses an exhibition of the Justin and Elisabeth Lang Collection of African Art at Queen's University, Ontario, by guest curators Marc Epprecht and Allison Goebel (2016–2018). This was a community-based exhibition that attempted to challenge the problematic history of colonial-era appropriation, collection and display of African art in Western museums. Members of the African and diasporic communities at Queen's and from the region were invited to select a piece or pieces from the collection and respond in a personal way. These contributions included short essays, poetry, art and personal reflections, some of which were captured in video form. This paper reflects on the decolonizing ambitions of the exhibition through engagement with the museology and decolonization literatures, as well as post-exhibition reflections by gallery staff and exhibition contributors.